Open Innovation and Value Creation in Crop Genetics - Müller, M.L.; Campos, Hugo (Springer, 2021)
The development of cultivars exhibiting improved climate resilience and containing effective input and agronomic traits and their adoption by growers and acceptance by supply chains, consumers, and society remain essential drivers of a successful agricultural strategy directed to feed the world and overcome the challenges brought by nature, an increasingly stringent regulatory environment, and an ever-growing population. In order to deliver on the daunting challenge of providing affordable, nutritious food to humankind, while reducing agriculture’s environmental footprint, new innovation models are needed.Open innovation is being adopted by seed companies in order to tap into the vast pool of human talent available beyond their boundaries and increase their ability to generate, adopt, develop, and bring to market novel technologies while building upon the increasing global community of innovators and harnessing the resources of venture capitalists. In addition, open innovation can help streamline product development processes, as well as lead to the exploration of novel markets which would otherwise go unexploited. At the same time, open innovation provides the means for other firms and entrepreneurs to gain access to technologies which would be beyond the scope of their development abilities but which can be leveraged to create significant value for their own customers and markets.This chapter provides an updated perspective on the most salient aspects of open innovation. Though its main focus is crop genetics and the development of improved cultivars, the general principles discussed also apply to other activities associated with the value chains linking agriculture and customers.